The Impact of Mobile-Assisted Language Learning (MALL) on Vocabulary Acquisition in Arabic as a Foreign Language - R. Al-Hashimi; M. Bauer (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the impact of Mobile-Assisted Language Learning (MALL) on vocabulary acquisition in learners of Arabic as a foreign language. As mobile technologies increasingly permeate educational settings, MALL has emerged as a promising approach to enhancing language learning efficiency, flexibility, and engagement. This research employed a qualitative explorative design to examine how mobile-based learning tools—such as digital dictionaries, flashcard applications, and interactive vocabulary platforms—contribute to learners’ mastery of Arabic vocabulary. Data were collected through classroom observations, semi-structured interviews, and learners’ reflective journals. Findings reveal that MALL facilitates increased learner autonomy, improves recall through spaced repetition, and provides immediate feedback that supports more effective vocabulary retention. Additionally, mobile tools were found to create a more personalized and motivating learning environment, contributing to higher levels of student engagement. However, the study also identifies challenges related to technological accessibility and inconsistent learner discipline when using mobile devices. Overall, the research concludes that MALL significantly enhances vocabulary acquisition in Arabic as a foreign language, provided that its implementation is supported by structured pedagogical strategies and adequate digital literacy training.